The diagnostic value of intraocular fluid analysis by polymerase chain reaction in Thai patients with uveitis - Kessara Pathanapitoon (2018)
Uveitis is a major cause of severe visual impairment throughout the world and can be initiated by various infectious and non-infectious causes. Early recognition of specific infections is important as the treatment with antimicrobial agents might stop the progression or even cure the eye disease. To determine the infectious causes of uveitis in Thailand, intraocular fluid samples of 100 HIV-negative patients and 47 HIV-positive patients with uveitis were examined using real-time PCR analysis for herpes simplex virus, varicella zoster virus, cytomegalovirus and Toxoplasma gondii. Positive PCR results were found in 33/100 (33%) HIV-negative patients and in 33/47 (70%) HIV-positive patients with uveitis. In Thailand, cytomegalovirus was identified as the most frequent cause of infectious uveitis in both HIV-negative and HIV-positive patients (49 and 91%, respectively). PCR analysis of intraocular samples in uveitis was a valuable diagnostic assay. The pattern of uveitis observed in the Far East differs from that found in the West. © 2011 Royal Society of Tropical Medicine and Hygiene.